2013
DOI: 10.1158/0008-5472.sabcs13-s1-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-01: The association between event-free survival and pathological complete response to neoadjuvant lapatinib, trastuzumab or their combination in HER2-positive breast cancer. Survival follow-up analysis of the NeoALTTO study (BIG 1-06)

Abstract: Background: The NeoALTTO study demonstrated a significantly higher breast pathological complete response (pCR) rate (NSABP definition – ypT0/is) with dual HER2 blockade using lapatinib and trastuzumab compared with single HER2 blockade using either lapatinib or trastuzumab (51.3% vs. 24.7% vs. 29.5%, respectively; p< 0.01 for both) in HER2 positive primary breast cancer (BC). A similar pattern was seen for locoregional pCR (ypT0/is ypN0) (Baselga J et al. Lancet 2012). Material and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…64 Updated preliminary data presented at the 2013 San Antonio Breast Cancer Symposium showed that patients who experienced a pathologic complete response had a better outcome than those who did not. 65 These studies thus confirm that the use of HER2-targeted therapy is important in the preoperative treatment of HER2 + primary breast cancer. Significant uncertainty remains regarding the optimal regimen of HER2 targeting.…”
supporting
confidence: 61%
“…64 Updated preliminary data presented at the 2013 San Antonio Breast Cancer Symposium showed that patients who experienced a pathologic complete response had a better outcome than those who did not. 65 These studies thus confirm that the use of HER2-targeted therapy is important in the preoperative treatment of HER2 + primary breast cancer. Significant uncertainty remains regarding the optimal regimen of HER2 targeting.…”
supporting
confidence: 61%
“…No cardiac dysfunctions were reported [48]. Patients who achieved pCR had significantly better EFS and OS compared with patients who had no pCR [49]. First DFS results of the ALTTO trial were presented at the ASCO meeting 2014.…”
Section: Dual Blockade Of the Her2-receptor With Trastuzumab And Lapamentioning
confidence: 99%
“…The pCR rates were higher in patients with hormone receptor-negative tumors than those of hormone receptor-positive tumors in all groups (61.3 vs. 41.6%). A recent update of the study demonstrated that patients who achieved pCR had significantly better event-free survival (EFS) (86% vs. 72%; HR, 0.38; P = 0.003) and OS (94% vs. 87%; HR 0.35; P = 0.005) compared with no pCR [ 34 ]. These results did not address the question of whether the higher pCR rate achieved with dual therapy translated into better EFS or OS because the NeoALTTO trial was underpowered to detect moderate differences in EFS and OS.…”
Section: Evidence For Improved Activity Of Combination Anti-hertherapmentioning
confidence: 99%